2015
DOI: 10.1002/hyp.10733
|View full text |Cite
|
Sign up to set email alerts
|

Estimating stream solute loads from fixed frequency sampling regimes: the importance of considering multiple solutes and seasonal fluxes in the design of long‐term stream monitoring networks

Abstract: Abstract:Reduced sampling frequency is known to increase the error associated with estimates of stream solute load. However, the extent to which the magnitude of error differs among commonly measured solutes and across seasons is unclear. In this study, a high sampling frequency data set from two forested streams (one upland-draining and one wetland-draining stream) in south-central Ontario was systematically sub-sampled to simulate weekly, fortnightly and monthly fixed frequency sampling regimes for 12 stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 63 publications
(127 reference statements)
3
6
0
Order By: Relevance
“…Good precisions could be achieved except when concentrations were variable (relative SEs of the concentrations were >~20%) and when there were not strong temporal patterns in concentrations (autocorrelation of the concentrations was <~0.3–0.4); and are consistent with the findings of Kerr et al. ().…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Good precisions could be achieved except when concentrations were variable (relative SEs of the concentrations were >~20%) and when there were not strong temporal patterns in concentrations (autocorrelation of the concentrations was <~0.3–0.4); and are consistent with the findings of Kerr et al. ().…”
Section: Discussionsupporting
confidence: 87%
“…Kerr et al. () indicated that solutes that had higher temporal variation in concentrations had poorer precisions when using a period‐weighted approach. Aulenbach () indicated that for suspended sediment with a relatively strong concentration–discharge relation, when the autocorrelation of regression‐model residual concentrations was >0.15, the composite method could improve upon regression‐model method load estimates.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the event-based export of P can contribute up to 40% to the seasonal and 19% to the annual export fluxes, which highlights the importance of monitoring stormflow events for flux estimation and process understanding. These results support the findings of numerous studies [9,11,18,31] which have found that time discrete sampling schemes at the monthly or bi-weekly time scale are unable to capture short-term changes in solute concentrations, and therefore can lead to a bias in load calculations. Ide et al [18] suggested that a certain number of monitored stormflow events are necessary to quantify export fluxes with low bias.…”
Section: Methodssupporting
confidence: 90%
“…Using this relationship, the solute concentration for the times without samples is estimated based on the measured discharge. The extrapolation methods differ in the method used to establish the discharge-solute relationship [9,20]. The interpolation models shown in Table 1 were applied using the R-package loadflex [20].…”
Section: Load Calculationsmentioning
confidence: 99%
See 1 more Smart Citation